2022
DOI: 10.1002/jcla.24473
|View full text |Cite
|
Sign up to set email alerts
|

A U‐shaped association between serum albumin with total triiodothyronine in adults

Abstract: Background Thyroid dysfunction is a common thyroid disorder in our life and its symptoms are non‐specific, therefore the diagnosis of thyroid dysfunction is important for patients. Albumin (ALB) can carry thyroid hormones to their sites of action as a way to achieve rapid delivery of thyroid hormones to the tissues. The purpose of this study was to investigate the relationship between serum ALB levels and total triiodothyronine (TT3) in adults. Methods Data from the 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“… 37 We found that patients with low T3 levels also had low albumin levels, consistent with the results of a study confirming an independent positive relationship between T3 and albumin levels. 38 Another interesting finding was that the C-peptide level was significantly lower in the low than normal T3 group. The C-peptide hormone is synthesized and released by the pancreas, along with insulin.…”
Section: Discussionmentioning
confidence: 93%
“… 37 We found that patients with low T3 levels also had low albumin levels, consistent with the results of a study confirming an independent positive relationship between T3 and albumin levels. 38 Another interesting finding was that the C-peptide level was significantly lower in the low than normal T3 group. The C-peptide hormone is synthesized and released by the pancreas, along with insulin.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, ALB was also assessed and reported as a marker of poor disease control along with traditional markers in diabetes mellitus, [ 27 ] hypertension, [ 28 , 29 ] metabolic syndrome, [ 30 , 31 ] and thyroiditis. [ 32 , 33 ] Hence, a combination of multiple indicators can considerably increase the diagnostic and predictive efficiency of PE compared with a single indicator. The markers we discovered, particularly FAR, have considerable potential in the prediction of severity for preeclampsia with no additional cost.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that, when LDL-C levels were <3.52 mmol/L values, LDL-C levels were negatively correlated with lumbar BMD in Chinese postmenopausal women ( 18 ). Other studies discovered a positive relationship between HDL-C and lumbar BMD and suggested that lipid metabolism plays a vital role in regulating BMD ( 19 , 20 ). However, Makovey et al observed that HDL-C levels were inversely associated with BMD in premenopausal women ( 21 ).…”
Section: Discussionmentioning
confidence: 99%